Nilai dan kepuasan pelanggan: Strategi meningkatkan loyalitas pelanggan melalui nilai dan kepuasan di era digital - Akbar, Moh Rafi (Maliki Interdisciplinary Journal, 2025)
This study discusses the influence of customer value and satisfaction on customer loyalty in the digital era. In the context of increasingly tight market competition, customer satisfaction is one of the main factors influencing loyalty, which can then provide competitive advantages for companies. Customer value, which includes emotional, social, performance, and price values, is identified as the main determinant of satisfaction. Customer satisfaction is measured based on the extent to which their consumption experience matches their expectations. The results of the study indicate that high value and satisfaction are positively correlated with customer loyalty, including in terms of repeat purchases and positive recommendations. Therefore, companies are advised to continue to improve the value and quality of service to maintain and expand their customer base.